COST REDUCTION STRATEGY IN PAPAYA PRODUCTION: IMPLEMENTING DMAIC AND LEAN FARM - Parcelino Prabowo, Rommy; Yudoko, Gatot (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Great Giant Pineapple (GGP) faced significant losses in papaya production in 2022, with actual costs reaching IDR 25,000/Kg against a budget of IDR 5,900/Kg, resulting in a IDR 4.2 billion loss. Plant care and maintenance, particularly fertilization and manual pesticide application, were the primary cost drivers. Utilizing the DMAIC methodology and SAP data, the research focused on cost reduction. Fertilization costs were dominated by materials, which were deemed unchangeable due to research-backed recommendations. Therefore, the study targeted labor efficiency in manual pesticide application. Cost-benefit analysis identified "Improvement Scenario 1" (layout: double-row, 1,8 meter, 3,25 meter operational road) as the most effective/best alternative for cost reduction. This scenario was selected for implementation to achieve cost efficiency in pesticide application, aiming to reverse the substantial losses incurred in papaya production. The project aimed to bring the cost closer to the budgeted amount, thus making the papaya business profitable.